A role for neurokinin 1 receptor expressing neurons in the paratrigeminal nucleus in bradykinin‐evoked cough in guinea‐pigs. (1st May 2020) - Driessen, Alexandria K.; McGovern, Alice E.; Behrens, Robert; Moe, Aung Aung Kywe; Farrell, Michael J.; Mazzone, Stuart B.
Abstract : Key points: Airway projecting sensory neurons arising from the jugular vagal ganglia terminate centrally in the brainstem paratrigeminal nucleus, synapsing upon neurons expressing the neurokinin 1 receptor. This study aimed to assess the involvement of paratrigeminal neurokinin 1 receptor neurons in the regulation of cough, breathing and airway defensive responses. Lesioning neurokinin 1 receptor expressing paratrigeminal neurons significantly reduced cough evoked by inhaled bradykinin but not inhaled ATP or tracheal mechanical stimulation. The reduction in bradykinin‐evoked cough was not accompanied by changes in baseline or evoked respiratory variables (e.g. frequency, volume or timing), animal avoidance behaviours or the laryngeal apnoea reflex. These findings warrant further investigations into targeting the jugular ganglia and paratrigeminal nucleus as a therapy for treating cough in disease. Abstract: Jugular vagal ganglia sensory neurons innervate the large airways and are thought to mediate cough and associated perceptions of airway irritations to a range of chemical irritants. The central terminals of jugular sensory neurons lie within the brainstem paratrigeminal nucleus, where postsynaptic neurons can be differentiated based on the absence or presence of the neurokinin 1 (NK1) receptor. Therefore, in the present study, we set out to test the hypothesis that NK1 receptor expressing paratrigeminal neurons play a role in cough evoked by inhaled chemical irritants. To test this, we performed selective neurotoxin lesions of NK1 receptor expressing neurons in the paratrigeminal nucleus in guinea‐pigs using substance P conjugated to saporin (SSP‐SAP). Sham lesion control or SSP‐SAP lesion guinea‐pigs received nebulised challenges, with the pan‐nociceptor stimulant bradykinin or the nodose ganglia specific stimulant adenosine 5′‐triphosphate (ATP), in conscious whole‐body plethysmography to study cough and associated behaviours. Laryngeal apnoea reflexes and cough evoked by mechanical stimulation of the trachea were additionally investigated in anaesthetised guinea‐pigs. SSP‐SAP significantly and selectively reduced the number of NK1 receptor expressing neurons in the paratrigeminal nucleus. This was associated with a significant reduction in bradykinin‐evoked cough, but not ATP‐evoked cough, mechanical cough or laryngeal apnoeic responses. These data provide further evidence for a role of jugular vagal pathways in cough, and additionally suggest an involvement of NK1 receptor expressing neurons in the paratrigeminal nucleus. Therefore, this neural pathway may provide novel therapeutic opportunities to treat conditions of chronic cough. Key points: Airway projecting sensory neurons arising from the jugular vagal ganglia terminate centrally in the brainstem paratrigeminal nucleus, synapsing upon neurons expressing the neurokinin 1 receptor. This study aimed to assess the involvement of paratrigeminal neurokinin 1 receptor neurons in the regulation of cough, breathing and airway defensive responses. Lesioning neurokinin 1 receptor expressing paratrigeminal neurons significantly reduced cough evoked by inhaled bradykinin but not inhaled ATP or tracheal mechanical stimulation. The reduction in bradykinin‐evoked cough was not accompanied by changes in baseline or evoked respiratory variables (e.g. frequency, volume or timing), animal avoidance behaviours or the laryngeal apnoea reflex. These findings warrant further investigations into targeting the jugular ganglia and paratrigeminal nucleus as a therapy for treating cough in disease.